(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
In 2023, after a full 20 years, the Republic of Croatia adopted a new legal framework for maritime domain with the enactment of the new Maritime Domain and Seaports Act. The new act addresses numerous technical issues related to Croatia’s maritime domain and aligns concessions on maritime domain with the current European legal framework. However, this act regulates in a new way two important areas crucial for the hospitality industry. Firstly, it provides a very precise legal regulation of beaches, an exceptional strategic resource, which were inadequately regulated in previous legislation. Seaside beaches now have their own precise division, an organized method of management, concessions, and very precisely defined freedom of access to the beaches. Furthermore, for the first time, the new act allows concessions on request, specifying the type of concessions that can be sought by a hotel, camp, or tourist resort. In this article, we want to highlight the novelties brought by the new legal regulation, focusing on beaches and concessions on request - which could be significantly important for the further development of higher category hotel and hospitality businesses, as well as providing a greater variety of services on the Croatian seacoast.